2005
DOI: 10.1177/160940690500400302
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Theory: A Case Study

Abstract: International attention is currently focused on alleviating health disparities through the adoption of new paradigms of research and the development of culturally relevant theories of health and illness. Yet, in spite of consistent calls to inform these deficiencies, the methodological trajectory from problem identification to theoretical development has remained relatively elusive. In this article, the authors present a case study of a systematic research methodology that resulted in a refined theory of socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…A profound strength of photovoice is that discussions and research directions are determined by the participants. Participants capture images of importance in their lives, lead discussions, identify issues, and work toward formulating solutions, thus becoming more entrenched in the research process (Carlson, Engebretson, & Chamberlain, 2005; Moffitt & Vollman, 2004). This is extremely empowering when used in connection with youth, whose voices can go unheard in research.…”
Section: Introductionmentioning
confidence: 99%
“…A profound strength of photovoice is that discussions and research directions are determined by the participants. Participants capture images of importance in their lives, lead discussions, identify issues, and work toward formulating solutions, thus becoming more entrenched in the research process (Carlson, Engebretson, & Chamberlain, 2005; Moffitt & Vollman, 2004). This is extremely empowering when used in connection with youth, whose voices can go unheard in research.…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach had the clear benefit of reducing the external pressures to produce 'findings' ahead of clarity about relationships -such a critical matter to our developing model. It assisted us to think about how the findings could contribute to ongoing theory building (Carlson, Engebretson, and Chamberlain 2005). The project achieved a high level of engagement within the organisation and generated a commitment to an ongoing process by both researchers and organisational staff.…”
Section: Projectmentioning
confidence: 96%
“…Finally, researchers, practitioners and clients have resources they can share within their communities and there is a reflexive process that can occur between research, practice and community domains (indicated in the far right hand panel of Figure 4). This community engagement also enables researchers to gain an understanding of the everyday life of the community and to generate rich data that may function to disrupt previously held views about particular communities and provide a deeper understanding of community life (Fine et al 2003;Carlson, Engebretson, and Chamberlain, 2005).…”
Section: The New Model -Action Research In Practicementioning
confidence: 99%
See 2 more Smart Citations